Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos, Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas; Grundmeier, Guido (Applied Surface Science)
Near ambient pressure XPS in nitrogen atmosphere was utilized to investigate gas-solid interactions within porous SiO2 films ranging from 30 to 75 nm thickness. The films were differentiated in terms of porosity and roughness. The XPS N1s core levels of the N2 gas in presence of the SiO2 samples showed variations in width, binding energy and line shape. The width correlated with the surface charge induced in the dielectric films upon X-ray irradiation. The observed different binding energies observed for the N1s peak can only partly be associated with intrinsic work function differences between the samples, opening the possibility that the effect of physisorption at room temperature could be detected by a shift in the measured binding energy. However, the signals also show an increasing asymmetry with rising surface charge. This might be associated with the formation of vertical electrical gradients within the dielectric porous thin films, which complicates the assignment of binding energy positions to specific surface-related effects. With the support of Monte Carlo and first principles density functional theory calculations, the observed shifts were discussed in terms of the possible formation of transitory dipoles upon N2 physisorption within the porous SiO2 films.
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Enhancement of the delamination resistance of adhesive film coated surface laser melted aluminum 7075-T6 alloy by aminophosphonic acid adsorption - Vieth, P.; Garthe, M.-A.; Voswinkel, Dietrich; Schaper, Mirko; Grundmeier, Guido (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Influence of proteins on the corrosion of a conventional and selective laser beam melted FeMn alloy in physiological electrolytes - Huang, Jingyuan; Orive, Alejandro Gonzalez; Krüger, Jan Tobias; Hoyer, Kay-Peter; Keller, Adrian; Grundmeier, Guido (Corrosion Science)
Keywords: General Materials Science; General Chemical Engineering; General Chemistry

Microstructure and corrosion properties of PBF-LB produced carbide nanoparticles additivated AlSi10Mg parts - Kusoglu, Ihsan Murat; Vieth, Pascal; Heiland, Steffen; Huber, Florian; Lüddecke, Arne; Ziefuss, Anna Rosa; Kwade, Arno; Schmidt, Michael; Schaper, Mirko; Barcikowski, Stephan; Grundmeier, Guido (Procedia CIRP)
Keywords: General Medicine

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Electrografting of BTSE: Zn films for advanced steel-aluminum joining by plastic deformation - Duderija, B.; González-Orive, A.; Schmidt, H.C.; Calderón, J.C.; Hordych, I.; Maier, H.J.; Homberg, W.; Grundmeier, G. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Rieker, Florian; Meinderink, Dennis; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)

Morphological Dynamics of Leukemia Cells on TiO2 Nanoparticle Coatings Studied by AFM - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Grundmeier, Guido; Camargo Amado, Ruben Jesus; Keller, Adrian (Applied Sciences)
Coatings of modified TiO2 nanoparticles (TiO2-m) have been shown to effectively and selectively trap non-adherent cancer cells, with an enormous potential for applications in photodynamic therapy (PDT). Leukemia cells have a remarkable affinity for TiO2-m coatings, adhering to the surface by membrane structures and exhibiting morphologic characteristics of amoeboid locomotion. However, the details of the cell–substrate interaction induced by the TiO2-m coating remain elusive. With the aim to obtain a better understanding of this phenomenon, leukemia cell adhesion to such coatings was characterized by atomic force microscopy (AFM) for short contact times up to 60 min. The cell and membrane morphological parameters mean cell height, contact area, cell volume, and membrane roughness were determined at different contact times. These results reveal cell expansion and contraction phases occurring during the initial stage of adhesion. Subsequently, the leukemic cells reach what appears to be a new resting state, characterized by pinning of the cell membrane by TiO2-m nanoparticle aggregates protruding from the coating surface.

Influence of thickness, homogeneity, and morphology of TiO2-m nanoparticle coatings on cancer cell adhesion - Garcia-Diosa, Jaime Andrés; Orive, Alejandro Gonzalez; Grundmeier, Guido; Keller, Adrian; Camargo-Amado, Rubén Jesús (Surface and Coatings Technology)

Nanoscale Surface Topography Modulates hIAPP Aggregation Pathways at Solid–Liquid Interfaces - Hanke, Marcel; Yang, Yu; Ji, Yuxin; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
The effects that solid–liquid interfaces exert on the aggregation of proteins and peptides are of high relevance for various fields of basic and applied research, ranging from molecular biology and biomedicine to nanotechnology. While the influence of surface chemistry has received a lot of attention in this context, the role of surface topography has mostly been neglected so far. In this work, therefore, we investigate the aggregation of the type 2 diabetes-associated peptide hormone hIAPP in contact with flat and nanopatterned silicon oxide surfaces. The nanopatterned surfaces are produced by ion beam irradiation, resulting in well-defined anisotropic ripple patterns with heights and periodicities of about 1.5 and 30 nm, respectively. Using time-lapse atomic force microscopy, the morphology of the hIAPP aggregates is characterized quantitatively. Aggregation results in both amorphous aggregates and amyloid fibrils, with the presence of the nanopatterns leading to retarded fibrillization and stronger amorphous aggregation. This is attributed to structural differences in the amorphous aggregates formed at the nanopatterned surface, which result in a lower propensity for nucleating amyloid fibrillization. Our results demonstrate that nanoscale surface topography may modulate peptide and protein aggregation pathways in complex and intricate ways.

Unraveling the interaction between doxorubicin and DNA origami nanostructures for customizable chemotherapeutic drug release - Ijäs, Heini; Shen, Boxuan; Heuer-Jungemann, Amelie; Keller, Adrian; Kostiainen, Mauri A; Liedl, Tim; Ihalainen, Janne A; Linko, Veikko (Nucleic Acids Research)
Abstract Doxorubicin (DOX) is a common drug in cancer chemotherapy, and its high DNA-binding affinity can be harnessed in preparing DOX-loaded DNA nanostructures for targeted delivery and therapeutics. Although DOX has been widely studied, the existing literature of DOX-loaded DNA-carriers remains limited and incoherent. Here, based on an in-depth spectroscopic analysis, we characterize and optimize the DOX loading into different 2D and 3D scaffolded DNA origami nanostructures (DONs). In our experimental conditions, all DONs show similar DOX binding capacities (one DOX molecule per two to three base pairs), and the binding equilibrium is reached within seconds, remarkably faster than previously acknowledged. To characterize drug release profiles, DON degradation and DOX release from the complexes upon DNase I digestion was studied. For the employed DONs, the relative doses (DOX molecules released per unit time) may vary by two orders of magnitude depending on the DON superstructure. In addition, we identify DOX aggregation mechanisms and spectral changes linked to pH, magnesium, and DOX concentration. These features have been largely ignored in experimenting with DNA nanostructures, but are probably the major sources of the incoherence of the experimental results so far. Therefore, we believe this work can act as a guide to tailoring the release profiles and developing better drug delivery systems based on DNA-carriers.

Scaling Up DNA Origami Lattice Assembly. - Xin, Y; Shen, B; Kostiainen, MA; Grundmeier, Guido; Castro, M; Linko, V; Keller, Adrian (Chemistry – A European Journal)

Protein Adsorption at Nanorough Titanium Oxide Surfaces: The Importance of Surface Statistical Parameters beyond Surface Roughness. - Yang, Y; Knust, S; Schwiderek, S; Qin, Q; Yun, Q; Grundmeier, Guido; Keller, Adrian (Nanomaterials)

Biotemplated Lithography of Inorganic Nanostructures (BLIN) for Versatile Patterning of Functional Materials - Piskunen, Petteri; Shen, Boxuan; Keller, Adrian; Toppari, J. Jussi; Kostiainen, Mauri A.; Linko, Veikko (ACS Applied Nano Materials)

DNA Nanostructures in the Fight Against Infectious Diseases. - Smith, DM; Keller, Adrian (Advanced NanoBiomed Research)

Adsorption of SARS-CoV-2 Spike Protein S1 at Oxide Surfaces Studied by High-Speed Atomic Force Microscopy. - Xin, Y; Grundmeier, Guido; Keller, Adrian (Advanced NanoBiomed Research)

Effect of nanoscale surface topography on the adsorption of globular proteins - Yang, Yu; Yu, Mingrui; Böke, Frederik; Qin, Qin; Hübner, René; Knust, Steffen; Schwiderek, Sabrina; Grundmeier, Guido; Fischer, Horst; Keller, Adrian (Applied Surface Science)

Effect of PAA-induced surface etching on the adhesion properties of ZnO nanostructured films - Meinderink, Dennis; Kielar, C.; Sobol, O.; Ruhm, L.; Rieker, F.; Nolkemper, K.; Orive, A.G.; Ozcan, O.; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Ion Beam Nanopatterning of Biomaterial Surfaces - Yang, Yu; Keller, Adrian (Applied Sciences)
Ion beam irradiation of solid surfaces may result in the self-organized formation of well-defined topographic nanopatterns. Depending on the irradiation conditions and the material properties, isotropic or anisotropic patterns of differently shaped features may be obtained. Most intriguingly, the periodicities of these patterns can be adjusted in the range between less than twenty and several hundred nanometers, which covers the dimensions of many cellular and extracellular features. However, even though ion beam nanopatterning has been studied for several decades and is nowadays widely employed in the fabrication of functional surfaces, it has found its way into the biomaterials field only recently. This review provides a brief overview of the basics of ion beam nanopatterning, emphasizes aspects of particular relevance for biomaterials applications, and summarizes a number of recent studies that investigated the effects of such nanopatterned surfaces on the adsorption of biomolecules and the response of adhering cells. Finally, promising future directions and potential translational challenges are identified.

Enhanced corrosion resistance of adhesive/galvanised steel interfaces by nanocrystalline ZnO thin film deposition and molecular adhesion promoting films - Grothe, Richard; Striewe, Jan Andre; Meinderink, Dennis; Tröster, Thomas; Grundmeier, Guido (The Journal of Adhesion)

Strain-Dependent Adsorption of Pseudomonas aeruginosa-Derived Adhesin-like Peptides at Abiotic Surfaces - Yang, Yu; Schwiderek, Sabrina; Grundmeier, Guido; Keller, Adrian (Micro)
Implant-associated infections are an increasingly severe burden on healthcare systems worldwide and many research activities currently focus on inhibiting microbial colonization of biomedically relevant surfaces. To obtain molecular-level understanding of the involved processes and interactions, we investigate the adsorption of synthetic adhesin-like peptide sequences derived from the type IV pili of the Pseudomonas aeruginosa strains PAK and PAO at abiotic model surfaces, i.e., Au, SiO2, and oxidized Ti. These peptides correspond to the sequences of the receptor-binding domain 128–144 of the major pilin protein, which is known to facilitate P. aeruginosa adhesion at biotic and abiotic surfaces. Using quartz crystal microbalance with dissipation monitoring (QCM-D), we find that peptide adsorption is material- as well as strain-dependent. At the Au surface, PAO(128–144) shows drastically stronger adsorption than PAK(128–144), whereas adsorption of both peptides is markedly reduced at the oxide surfaces with less drastic differences between the two sequences. These observations suggest that peptide adsorption is influenced by not only the peptide sequence, but also peptide conformation. Our results furthermore highlight the importance of molecular-level investigations to understand and ultimately control microbial colonization of surfaces.

Magnesium-Free Immobilization of DNA Origami Nanostructures at Mica Surfaces for Atomic Force Microscopy - Xin, Yang; Zargariantabrizi, Amir Ardalan; Grundmeier, Guido; Keller, Adrian (Molecules)
DNA origami nanostructures (DONs) are promising substrates for the single-molecule investigation of biomolecular reactions and dynamics by in situ atomic force microscopy (AFM). For this, they are typically immobilized on mica substrates by adding millimolar concentrations of Mg2+ ions to the sample solution, which enable the adsorption of the negatively charged DONs at the like-charged mica surface. These non-physiological Mg2+ concentrations, however, present a serious limitation in such experiments as they may interfere with the reactions and processes under investigation. Therefore, we here evaluate three approaches to efficiently immobilize DONs at mica surfaces under essentially Mg2+-free conditions. These approaches rely on the pre-adsorption of different multivalent cations, i.e., Ni2+, poly-l-lysine (PLL), and spermidine (Spdn). DON adsorption is studied in phosphate-buffered saline (PBS) and pure water. In general, Ni2+ shows the worst performance with heavily deformed DONs. For 2D DON triangles, adsorption at PLL- and in particular Spdn-modified mica may outperform even Mg2+-mediated adsorption in terms of surface coverage, depending on the employed solution. For 3D six-helix bundles, less pronounced differences between the individual strategies are observed. Our results provide some general guidance for the immobilization of DONs at mica surfaces under Mg2+-free conditions and may aid future in situ AFM studies.

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung und Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Koch, Leon; Ebbert, Christoph; Grundmeier, Guido

Durability of nanolayer Ti–Al–O–N hard coatings under simulated polycarbonate melt processing conditions - Brögelmann, T; Bobzin, K; Grundmeier, Guido; de los Arcos, T; Kruppe, N C; Schwiderek, S; Carlet, M (Journal of Physics D: Applied Physics)
Keywords: Surfaces; Coatings and Films; Acoustics and Ultrasonics; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Atomic Layer Deposition of Copper Metal Films from Cu(acac) 2 and Hydroquinone Reductant - Tripathi, Tripurari Sharan; Wilken, Martin; Hoppe, Christian; de los Arcos, Teresa; Grundmeier, Guido; Devi, Anjana; Karppinen, Maarit (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos de Pedro, Maria Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)

Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

Effect of DNA Origami Nanostructures on hIAPP Aggregation - Hanke, Marcel; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Nanomaterials)
The aggregation of human islet amyloid polypeptide (hIAPP) plays a major role in the pathogenesis of type 2 diabetes mellitus (T2DM), and numerous strategies for controlling hIAPP aggregation have been investigated so far. In particular, several organic and inorganic nanoparticles (NPs) have shown the potential to influence the aggregation of hIAPP and other amyloidogenic proteins and peptides. In addition to conventional NPs, DNA nanostructures are receiving more and more attention from the biomedical field. Therefore, in this work, we investigated the effects of two different DNA origami nanostructures on hIAPP aggregation. To this end, we employed in situ turbidity measurements and ex situ atomic force microscopy (AFM). The turbidity measurements revealed a retarding effect of the DNA nanostructures on hIAPP aggregation, while the AFM results showed the co-aggregation of hIAPP with the DNA origami nanostructures into hybrid peptide–DNA aggregates. We assume that this was caused by strong electrostatic interactions between the negatively charged DNA origami nanostructures and the positively charged peptide. Most intriguingly, the influence of the DNA origami nanostructures on hIAPP aggregation differed from that of genomic double-stranded DNA (dsDNA) and appeared to depend on DNA origami superstructure. DNA origami nanostructures may thus represent a novel route for modulating amyloid aggregation in vivo.

Protein-Assisted Room-Temperature Assembly of Rigid, Immobile Holliday Junctions and Hierarchical DNA Nanostructures - Ramakrishnan, Saminathan; Subramaniam, Sivaraman; Kielar, Charlotte; Grundmeier, Guido; Stewart, A. Francis; Keller, Adrian (Molecules)
Immobile Holliday junctions represent not only the most fundamental building block of structural DNA nanotechnology but are also of tremendous importance for the in vitro investigation of genetic recombination and epigenetics. Here, we present a detailed study on the room-temperature assembly of immobile Holliday junctions with the help of the single-strand annealing protein Redβ. Individual DNA single strands are initially coated with protein monomers and subsequently hybridized to form a rigid blunt-ended four-arm junction. We investigate the efficiency of this approach for different DNA/protein ratios, as well as for different DNA sequence lengths. Furthermore, we also evaluate the potential of Redβ to anneal sticky-end modified Holliday junctions into hierarchical assemblies. We demonstrate the Redβ-mediated annealing of Holliday junction dimers, multimers, and extended networks several microns in size. While these hybrid DNA–protein nanostructures may find applications in the crystallization of DNA–protein complexes, our work shows the great potential of Redβ to aid in the synthesis of functional DNA nanostructures under mild reaction conditions.

Self-assembly of highly ordered DNA origami lattices at solid-liquid interfaces by controlling cation binding and exchange - Xin, Yang; Martinez Rivadeneira, Salvador; Grundmeier, Guido; Castro, Mario; Keller, Adrian (Nano Research)
Abstract The surface-assisted hierarchical self-assembly of DNA origami lattices represents a versatile and straightforward method for the organization of functional nanoscale objects such as proteins and nanoparticles. Here, we demonstrate that controlling the binding and exchange of different monovalent and divalent cation species at the DNA-mica interface enables the self-assembly of highly ordered DNA origami lattices on mica surfaces. The development of lattice quality and order is quantified by a detailed topological analysis of high-speed atomic force microscopy (HS-AFM) images. We find that lattice formation and quality strongly depend on the monovalent cation species. Na + is more effective than Li + and K + in facilitating the assembly of high-quality DNA origami lattices, because it is replacing the divalent cations at their binding sites in the DNA backbone more efficiently. With regard to divalent cations, Ca 2+ can be displaced more easily from the backbone phosphates than Mg 2+ and is thus superior in guiding lattice assembly. By independently adjusting incubation time, DNA origami concentration, and cation species, we thus obtain a highly ordered DNA origami lattice with an unprecedented normalized correlation length of 8.2. Beyond the correlation length, we use computer vision algorithms to compute the time course of different topological observables that, overall, demonstrate that replacing MgCl 2 by CaCl 2 enables the synthesis of DNA origami lattices with drastically increased lattice order.

Quantitative Assessment of Tip Effects in Single‐Molecule High‐Speed Atomic Force Microscopy Using DNA Origami Substrates - Kielar, Charlotte; Zhu, Siqi; Grundmeier, Guido; Keller, Adrian (Angewandte Chemie International Edition)

Dynamics of lattice defects in mixed DNA origami monolayers - Xin, Yang; Ji, Xueyin; Grundmeier, Guido; Keller, Adrian (Nanoscale)
DNA origami lattice formation at solid–liquid interfaces is surprisingly resilient toward the incorporation of DNA origami impurities with different shapes.

Cryopreservation of DNA Origami Nanostructures - Xin, Yang; Kielar, Charlotte; Zhu, Siqi; Sikeler, Christoph; Xu, Xiaodan; Möser, Christin; Grundmeier, Guido; Liedl, Tim; Heuer‐Jungemann, Amelie; Smith, David M.; Keller, Adrian (Small)

Challenges and Perspectives of DNA Nanostructures in Biomedicine - Keller, Adrian; Linko, Veikko (Angewandte Chemie International Edition)

Amyloid aggregation at solid-liquid interfaces: Perspectives of studies using model surfaces - Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Arranging Small Molecules with Subnanometer Precision on DNA Origami Substrates for the Single‐Molecule Investigation of Protein–Ligand Interactions - Huang, Jingyuan; Suma, Antonio; Cui, Meiying; Grundmeier, Guido; Carnevale, Vincenzo; Zhang, Yixin; Kielar, Charlotte; Keller, Adrian (Small Structures)

Molecular adhesion science and engineering of nanostructured poly(acrylic acid)/metal oxide interfaces - Meinderink, Dennis
Das grundlegende Verständnis von makroskopischen Haftungsphänomenen beginnt bei der Analyse von molekularen Wechselwirkungen unter kontrollierten Bedingungen (Materialeigenschaften, chemische Oberflächenzusammensetzung, und weiteren Einflussfaktoren wie z.B. pH-Wert, Elektrolytzusammensetzung). In dieser Arbeit wurden die molekularen und makroskopischen Haftungseigenschaften von makromolekularer Poly(acrylsäure) (PAA) als potenzieller Haftungsvermittler auf Edelstahl und verschiedenen nanostrukturierten Zinkoxid (ZnO) Oberflächen untersucht, die mittels elektrochemischer und hydrothermalen Abscheidemethoden auf Edelstahl und feuerverzinktem Stahl (HDG) abgeschieden wurden. Molekulare Haftungsmechanismen zwischen PAA und ZnO basierend auf multi-koordinativen Bindungen in Abhängigkeit von der Oberflächenchemie und der Verweilzeit konnten mit der s.g. Einzelmolekülspektroskopie aufgeklärt werden. Die Ergebnisse aus weiteren makroskopischen Enthaftungsexperimenten und Rückseitenanalytik bei der Verwendung von verdünnten, wässrigen PAA-Lösungen zur Vorbehandlung von nanostrukturierten ZnO Filmen auf HDG Stahl untermauerten die starken Wechselwirkungen zwischen ZnO-PAA. Mittels Elektropolymerisation abgeschiedene PAA Filme zeigten eine signifikante Steigerung in den makroskopischen Haftungseigenschaften bei einem ausgewählten Model-Epoxid-Amin-Klebstoff auf Edelstahl. Die Kombination von ZnO Tetrapoden (ZnO TP) und PAA als hybridische, haftungsverbessernde Sprühbeschichtungen aus wässrigen Dispersionen auf Poly(propylen) Folien bestätigten, sowohl die chemischen, als auch mechanischen Haftungseigenschaften von nanostrukturierten ZnO/PAA Interphasen. Daher können PAA/Metalloxid-Grenzflächen die Tür in diversen technischen Ansätzen für innovative Anwendungen öffnen, wie z.B. in Sprühapplikationstechniken.

Spray pyrolysis of thin adhesion-promoting ZnO films on ZnMgAl coated steel - Grothe, R.; Knust, S.; Meinderink, Dennis; Voigt, M.; Orive, A. González; Grundmeier, Guido (Surface and Coatings Technology)

Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Single-Molecule Desorption Studies of Poly(acrylic acid) at Electrolyte/Oxide/TiAlN Interfaces - Schwiderek, Sabrina; Orive, Alejandro G.; Karimi Aghda, Soheil; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Langmuir)

Characterisation of micropores in plasma deposited SiO x films by means of positron annihilation lifetime spectroscopy - Hoppe, C; Mitschker, F; Butterling, M; Liedke, M O; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Wagner, A; Grundmeier, Guido (Journal of Physics D: Applied Physics)

Influence of dielectric barrier plasma treatment of ZnMgAl alloy‐coated steel on the adsorption of organophosphonic acid monolayers - Knust, Steffen; Kuhlmann, Andreas; Orive, Alejandro G.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Surface and Interface Analysis)

Self-Assembly of Fibrinogen in Aqueous, Thrombin-Free Solutions of Variable Ionic Strengths - Hämisch, Benjamin; Büngeler, Anne; Kielar, Charlotte; Keller, Adrian; Strube, Oliver; Huber, Klaus (Langmuir)

Enhancing the stability of DNA origami nanostructures: staple strand redesign versus enzymatic ligation - Ramakrishnan, Saminathan; Schärfen, Leonard; Hunold, Kristin; Fricke, Sebastian; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian; Krainer, Georg (Nanoscale)
Merging of bridging staples with adjacent oligonucleotide sequences leads to a moderate increase of DNA origami stability, while enzymatic ligation after assembly yields a reinforced nanostructure with superior stability at up to 37 °C and in the presence of 6 M urea.

Effect of Staple Age on DNA Origami Nanostructure Assembly and Stability - Kielar, Charlotte; Xin, Yang; Xu, Xiaodan; Zhu, Siqi; Gorin, Nelli; Grundmeier, Guido; Möser, Christin; Smith, David M.; Keller, Adrian (Molecules)
DNA origami nanostructures are widely employed in various areas of fundamental and applied research. Due to the tremendous success of the DNA origami technique in the academic field, considerable efforts currently aim at the translation of this technology from a laboratory setting to real-world applications, such as nanoelectronics, drug delivery, and biosensing. While many of these real-world applications rely on an intact DNA origami shape, they often also subject the DNA origami nanostructures to rather harsh and potentially damaging environmental and processing conditions. Furthermore, in the context of DNA origami mass production, the long-term storage of DNA origami nanostructures or their pre-assembled components also becomes an issue of high relevance, especially regarding the possible negative effects on DNA origami structural integrity. Thus, we investigated the effect of staple age on the self-assembly and stability of DNA origami nanostructures using atomic force microscopy. Different harsh processing conditions were simulated by applying different sample preparation protocols. Our results show that staple solutions may be stored at −20 °C for several years without impeding DNA origami self-assembly. Depending on DNA origami shape and superstructure, however, staple age may have negative effects on DNA origami stability under harsh treatment conditions. Mass spectrometry analysis of the aged staple mixtures revealed no signs of staple fragmentation. We, therefore, attribute the increased DNA origami sensitivity toward environmental conditions to an accumulation of damaged nucleobases, which undergo weaker base-pairing interactions and thus lead to reduced duplex stability.

Real-Time Observation of Superstructure-Dependent DNA Origami Digestion by DNase I Using High-Speed Atomic Force Microscopy. - Ramakrishnan, S; Shen, B; Kostiainen, MA; Grundmeier, Guido; Keller, Adrian; Linko, V (ChemBioChem)

DNA origami directed 3D nanoparticle superlattice via electrostatic assembly. - Julin, S; Korpi, A; Shen, B; Liljeström, V; Ikkala, O; Keller, Adrian; Linko, V; Kostiainen, MA (Nanoscale)

Effect of Terminal Modifications on the Adsorption and Assembly of hIAPP(20–29) - Hajiraissi, Roozbeh; Hanke, Marcel; Gonzalez Orive, Alejandro; Duderija, Belma; Hofmann, Ulrike; Zhang, Yixin; Grundmeier, Guido; Keller, Adrian (ACS Omega)

Spray coating of poly(acrylic acid)/ZnO tetrapod adhesion promoting nanocomposite films for polymer laminates - Meinderink, Dennis; Nolkemper, Karlo J.R.; Bürger, Julius; Orive, Alejandro G.; Lindner, Jörg K.N.; Grundmeier, Guido (Surface and Coatings Technology)

Low-Temperature Plasma-Enhanced Atomic Layer Deposition of Tin(IV) Oxide from a Functionalized Alkyl Precursor: Fabrication and Evaluation of SnO2-Based Thin-Film Transistor Devices - Mai, Lukas; Zanders, David; Subaşı, Ersoy; Ciftyurek, Engin; Hoppe, Christian; Rogalla, Detlef; Gilbert, Wolfram; de los Arcos de Pedro, Maria Teresa; Schierbaum, Klaus; Grundmeier, Guido; Bock, Claudia; Devi, Anjana (ACS Applied Materials & Interfaces)

Potential Precursor Alternatives to the Pyrophoric Trimethylaluminium for the Atomic Layer Deposition of Aluminium Oxide - Mai, Lukas; Boysen, Nils; Zanders, David; de los Arcos de Pedro, Maria Teresa; Mitschker, Felix; Mallick, Bert; Grundmeier, Guido; Awakowicz, Peter; Devi, Anjana (Chemistry – A European Journal)

Surface modification of ZnMgAl-coated steel by dielectric-barrier discharge plasma - Knust, Steffen; Kuhlmann, Andreas; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (RSC Advances)
Correlation between atmospheric DBD plasma-induced surface chemical changes on a ZnMgAl alloy coating and the resulting adhesive properties.

Analyse und Optimierung des Korrosions- und Alterungsverhaltens von hybriden Strukturen aus Metallen und CFK - Striewe, Jan André; Tröster, Thomas; Kowatz, Jannik; Meschut, Gerson; Grothe, Richard; Grundmeier, Guido

Analyse und Optimierung des Korrosions- und Alterungsverhaltens von hybriden Strukturen aus Metallen und CFK - Grothe, R.; Striewe, Jan André; Kowatz, Jannik; Grundmeier, Guido; Tröster, Thomas; Meschut, Gerson

Water adsorption and capillary bridge formation on silica micro-particle layers modified with perfluorinated organosilane monolayers - Giner, Ignacio; Torun, Boray; Han, Yan; Duderija, Belma; Meinderink, Dennis; Orive, Alejandro González; de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Tiemann, Michael; Schmid, Hans-Joachim; Grundmeier, Guido (Applied Surface Science)
Monodisperse micron-sized silica particle monolayers deposited onto plasma-grown SiOx-ultra-thin films have been used as reference systems to investigate wetting, water adsorption and capillary bridge formation as a function of silica surface functionalization. 1H,1H, 2H,2H perfluorooctyltriethoxysil (FOTS) monolayers, have been deposited on the respective surfaces by means of chemical vapor deposition resulting in macroscopically low energy surfaces. X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) reflection absorption spectroscopy confirmed the monolayer formation. Water adsorption isotherms were studied by a combination of in-situ FTIR reflection spectroscopy and quartz crystal microbalance (QCM) while macroscopic wetting was analysed by contact angle measurements. The comparative data evaluation indicates that the macroscopic wetting behaviour was changed as expected, however, that water nanodroplets formed both at intrinsic defects of the FOTS monolayer and at the FOTS/SiOx interface. Capillary bridges of liquid water are dominantly formed in the confined particle contact areas and between surface asperities on the particles. The comparison of wetting, adsorption and capillary bridge formation shows that the hydrophobization of porous materials by organosilane monolayers leads to the formation of morphology dependent nanoscopic defects that act as sites for preferential capillary bridge formation.

Dynamics of DNA Origami Lattice Formation at Solid–Liquid Interfaces - Kielar, Charlotte; Ramakrishnan, Saminathan; Fricke, Sebastian; Grundmeier, Guido; Keller, Adrian (ACS Applied Materials & Interfaces)

Structural stability of DNA origami nanostructures under application-specific conditions - Ramakrishnan, Saminathan; Ijäs, Heini; Linko, Veikko; Keller, Adrian (Computational and Structural Biotechnology Journal)

Pharmacophore Nanoarrays on DNA Origami Substrates as a Single-Molecule Assay for Fragment-Based Drug Discovery - Kielar, Charlotte; Reddavide, Francesco V.; Tubbenhauer, Stefan; Cui, Meiying; Xu, Xiaodan; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Angewandte Chemie International Edition)

Superstructure-Dependent Loading of DNA Origami Nanostructures with a Groove-Binding Drug - Kollmann, Fabian; Ramakrishnan, Saminathan; Shen, Boxuan; Grundmeier, Guido; Kostiainen, Mauri A.; Linko, Veikko; Keller, Adrian (ACS Omega)

Directed Protein Adsorption Through DNA Origami Masks - Ramakrishnan, Saminathan; Grundmeier, Guido; Keller, Adrian (DNA Nanotechnology: Methods and Protocols)

On the Stability of DNA Origami Nanostructures in Low-Magnesium Buffers - Kielar, Charlotte; Xin, Yang; Shen, Boxuan; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Angewandte Chemie International Edition)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Ultrasound-mediated deposition and cytocompatibility of apatite-like coatings on magnesium alloys - Liu, Chen-Ni; Böke, Frederik; Gebhard, Maximilian; Devi, Anjana; Fischer, Horst; Keller, Adrian; Grundmeier, Guido (Surface and Coatings Technology)

Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS - Hajiraissi, Roozbeh; Hanke, Marcel; Yang, Yu; Duderija, Belma; Gonzalez Orive, Alejandro; Grundmeier, Guido; Keller, Adrian (Langmuir)

Determination of the refractive indices of ionic liquids by ellipsometry, and their application as immersion liquids - Wu, Xia; Muntzeck, Maren; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Wilhelm, René; Wagner, Thorsten (Applied Optics)

Luminescent Nd2S3 thin films: a new chemical vapour deposition route towards rare-earth sulphides - Cwik, Stefan; Beer, Sebastian M. J.; Schmidt, Marcel; Gerhardt, Nils C.; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Weßing, Jana; Giner, Ignacio; Hofmann, Martin; Grundmeier, Guido; Wieck, Andreas D.; Devi, Anjana (Dalton Transactions)
Development of two new neodymium containing precursors and their successful implementation in the MOCVD of luminescent Nd2S3 thin films.

Improved homogeneity of plasma and coating properties using a lance matrix gas distribution in MW-PECVD - Kirchheim, Dennis; Wilski, Stefan; Jaritz, Montgomery; Mitschker, Felix; Oberberg, Moritz; Trieschmann, Jan; Banko, Lars; Brochhagen, Markus; Schreckenberg, Rabea; Hopmann, Christian; Böke, Marc; Benedikt, Jan; et al. (Journal of Coatings Technology and Research)

Validation of a Terminally Amino Functionalized Tetra‐Alkyl Sn(IV) Precursor in Metal–Organic Chemical Vapor Deposition of SnO 2 Thin Films: Study of Film Growth Characteristics, Optical, and Electrical Properties - Zanders, David; Ciftyurek, Engin; Hoppe, Christian; de los Arcos de Pedro, Maria Teresa; Kostka, Aleksander; Rogalla, Detlef; Grundmeier, Guido; Schierbaum, Klaus Dieter; Devi, Anjana (Advanced Materials Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

PEALD of SiO2 and Al2O3 Thin Films on Polypropylene: Investigations of the Film Growth at the Interface, Stress, and Gas Barrier Properties of Dyads - Gebhard, Maximilian; Mai, Lukas; Banko, Lars; Mitschker, Felix; Hoppe, Christian; Jaritz, Montgomery; Kirchheim, Dennis; Zekorn, Christoph; de los Arcos de Pedro, Maria Teresa; Grochla, Dario; Dahlmann, Rainer; Grundmeier, Guido; et al. (ACS Applied Materials & Interfaces)

Combined in situ infrared reflection absorption spectroscopy-quartz crystal microbalance investigation of the initial growth stages of plasma-deposited SiO x on polypropylene - Dietrich, J.; Hoppe, C.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Contributions to Plasma Physics)

Decoupling of ion- and photon-activation mechanisms in polymer surfaces exposed to low-temperature plasmas - Budde, Maik; Corbella, Carles; Große-Kreul, Simon; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; von Keudell, Achim (Plasma Processes and Polymers)

Water assisted atomic layer deposition of yttrium oxide using tris(N,N′-diisopropyl-2-dimethylamido-guanidinato) yttrium(iii): process development, film characterization and functional properties - Mai, Lukas; Boysen, Nils; Subaşı, Ersoy; de los Arcos de Pedro, Maria Teresa; Rogalla, Detlef; Grundmeier, Guido; Bock, Claudia; Lu, Hong-Liang; Devi, Anjana (RSC Advances)
A new water assisted atomic layer deposition (ALD) process was developed using the yttrium tris-guanidinate precursor which resulted in device quality thin films.

Comparative study on the deposition of silicon oxide permeation barrier coatings for polymers using hexamethyldisilazane (HMDSN) and hexamethyldisiloxane (HMDSO) - Mitschker, F; Schücke, L; Hoppe, Ch; Jaritz, M; Dahlmann, R; de los Arcos de Pedro, Maria Teresa; Hopmann, Ch; Grundmeier, Guido; Awakowicz, P (Journal of Physics D: Applied Physics)

Influence of average ion energy and atomic oxygen flux per Si atom on the formation of silicon oxide permeation barrier coatings on PET - Mitschker, F; Wißing, J; Hoppe, Ch; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido; Awakowicz, P (Journal of Physics D: Applied Physics)

Connection between target poisoning and current waveforms in reactive high-power impulse magnetron sputtering of chromium - Layes, Vincent; Corbella, Carles; Monjé, Sascha; Schulz-von der Gathen, Volker; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Plasma Sources Science and Technology)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, A.; Grundmeier, Guido (Applied Surface Science)

Analysis of polymer/oxide interfaces under ambient conditions – An experimental perspective - González-Orive, A.; Giner, I.; de los Arcos de Pedro, Maria Teresa; Keller, A.; Grundmeier, G. (Applied Surface Science)

Graphene oxide as flexibilizer for epoxy amine resins - Wolk, Andreas; Rosenthal, Marta; Weiß, Julia; Voigt, Markus; Wesendahl, Jan-Niklas; Hartmann, Marc; Grundmeier, Guido; Wilhelm, Rene; Meschut, Gerson; Tiemann, Michael; Bremser, Wolfgang (Progress in Organic Coatings)
Different types of reduced graphene oxide and graphene oxide particles have been studied regarding their influence on the curing behaviour of epoxy-amine resins. Especially the specific surface area of reduced graphene oxide was selectively influenced by controlled drying of the material. The different types of reduced graphene oxide particles were used to produce epoxy-amine composites that significantly change their curing behaviour and mechanical properties. A variety of surface areas and compositions were prepared by combination of a fast heating rate and different drying methods. The combination of freeze drying with a fast heating rate leads to a large specific surface area of 680 m2/g. The morphologies of the particles were observed by scanning electron microscope and the BET surface area was measured with nitrogen-physisorption. The exfoliation quality was measured by XRD. The generated graphene oxide and thermally reduced graphene oxide particles were mixed with epoxy-amine resin. The curing behaviour was studied with rheological and differential scanning calorimetry (DSC) measurements. We observed that different surface functionalities lowers the Glass transition temperature and the gel time of an epoxy-amine curing system. In addition, we found that generated graphene oxide acts as flexibilizer. An increase of the deformation from 2.5 mm to 3.1 mm was measured by Erichsen Cupping Test.

Corrosion properties of bioresorbable FeMn-Ag alloys prepared by selective laser melting - Wiesener, Markus; Peters, K.; Taube, Alexander; Keller, Adrian; Hoyer, Kay-Peter; Niendorf, Thomas; Grundmeier, Guido (Materials and Corrosion)

Cation-Induced Stabilization and Denaturation of DNA Origami Nanostructures in Urea and Guanidinium Chloride - Ramakrishnan, Saminathan; Krainer, Georg; Grundmeier, Guido; Schlierf, Michael; Keller, Adrian (Small)

Analysis of acid-base interactions at Al 2 O 3 (11-20) interfaces by means of single molecule force spectroscopy - Mosebach, Bastian; Ozkaya, Berkem; Giner, Ignacio; Keller, Adrian; Grundmeier, Guido (Applied Surface Science)

Scanning Kelvin probe blister studies of the delamination of epoxy films on organosilane modified ZnMgAl alloy coated steel - Grothe, R.; Wiesing, M.; Giner, I.; Meinderink, Dennis; Grundmeier, Guido (Materials and Corrosion)

Electropolymerization of acrylic acid on carbon fibers for improved epoxy/fiber adhesion - Bauer, Andreas; Meinderink, Dennis; Giner, Ignacio; Steger, Helmut; Weitl, Johann; Grundmeier, Guido (Surface and Coatings Technology)

A Contribution to explain the Mechanisms of Adhesive Wear in Plastics Processing by example of Polycarbonate - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

UHV AFM based colloidal probe studies of adhesive properties of VAlN hard coatings - Wiesing, M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Applied Surface Science)

Influence of PE-CVD and PE-ALD on defect formation in permeation barrier films on PET and correlation to atomic oxygen fluence - Mitschker, F; Steves, S; Gebhard, M; Rudolph, M; Schücke, L; Kirchheim, D; Jaritz, M; Brochhagen, M; Hoppe, Ch; Dahlmann, R; Böke, M; Benedikt, J; et al. (Journal of Physics D: Applied Physics)

Unearthing [3-(Dimethylamino)propyl]aluminium(III) Complexes as Novel Atomic Layer Deposition (ALD) Precursors for Al2O3: Synthesis, Characterization and ALD Process Development - Mai, Lukas; Gebhard, Maximilian; de los Arcos de Pedro, Maria Teresa; Giner, Ignacio; Mitschker, Felix; Winter, Manuela; Parala, Harish; Awakowicz, Peter; Grundmeier, Guido; Devi, Anjana (Chemistry - A European Journal)

Composite targets in HiPIMS plasmas: Correlation of in-vacuum XPS characterization and optical plasma diagnostics - Layes, Vincent; Monje, Sascha; Corbella, Carles; Schulz-von der Gathen, Volker; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 2) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

Influence of organic surface chemistry on the nucleation of plasma deposited SiOxfilms - Hoppe, C; Mitschker, F; Giner, I; de los Arcos de Pedro, Maria Teresa; Awakowicz, P; Grundmeier, G (Journal of Physics D: Applied Physics)

Species transport on the target during high power impulse magnetron sputtering - Layes, V.; Monje, S.; Corbella, C.; Trieschmann, J.; de los Arcos de Pedro, Maria Teresa; von Keudell, A. (Applied Physics Letters)